Pengelolaan Dana Alokasi Umum (DAU), Alokasi Khusus (DAK), dan Dana Bagi Hasil Pajak (DBHP) di Provinsi Sumatra Utara - Malau, Pastriono Leonarda; Manik, Dwi Verasuna; Tobing, Winda Sartika Lumban; Pulungan, Walda Ronia (Asosiasi Dosen Akuntansi Indonesia, 2023)
The purpose of this study is to analyze the effect of General Allocation Fund (DAU), Special Allocation Fund (DAK), and Tax Revenue Sharing on Poverty in North Sumatra Province. The analysis used in this study is panel data analysis, with panel data of 33 districts/cities in 2014-2020 obtained from BPS North Sumatra. The results obtained from this research are: General Allocation Fund has a negative effect on Poverty in North Sumatra Province; Special Allocation Fund has a negative effect on Poverty in North Sumatra Province; Tax Revenue Sharing has a positive effect on Poverty in North Sumatra Province. General Allocation Fund, Special Allocation Fund, and Tax Revenue Sharing have a significant effect on GRDPHB of North Sumatra Province with a determination coefficient of 99.54 percent. The dominant variable influencing Poverty in North Sumatra Province is the General Allocation Fund.